The effect of environmental temperature on time motion characteristics of soccer players in the Australian A League - Janse de Jonge, X.; Nosek, P.; Clark, A.; Everett, K.; Hillebrandt, H. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Sporting performance is understood to be negatively impacted in hot environments. In Australia the professional A League is played over the summer season. The size of the continent and the fact that some matches are played in New Zealand means that there is a large variation in environmental conditions between matches in the A League. This study aimed to examine the effect of environmental temperature on time-motion characteristics in a soccer team competing in the A League. Fifteen male soccer players (age 27 ± 5 yrs; body mass 81 ± 7 kg; height 183 ± 5 cm) from a professional soccer team volunteered for this project. They wore 5 Hz GPS units (MinimaxX, Catapult Innovations, Australia) during A League matches and 67 full game files were analysed for High Speed Activity (HSA) at >14.4 km/h, Low Speed Activity (LSA) at <14.4 km/h and total distance. Each half of the game was analysed and then divided into three equal periods for further analysis. The total number of match files was divided in half based on environmental temperature using the median split technique. Match files were excluded for the median temperature and to ensure equal distribution of the different playing positions resulting in 27 match files for each environmental condition. Mixed measures ANOVAs (with factor temperature and repeated measures for halves and the six periods) were performed. The mean temperature for the cool matches was 16ºC (range 9-19) and for warm matches was 23ºC (range 21-28). The ANOVAs for halves showed a significant decrease from first to second half for total and LSA distance and no significant interaction with temperature for any of the measures. For the six periods of the match a significant greater total, LSA and HSA distance was covered in the first period than all other periods, except for the first period of the second half for HSA. Furthermore an interaction between temperature and playing period was found for total and LSA distance with a significantly greater drop in both distances from the first to the fifth period in the warm condition compared to the cool condition. For HSA distance no significant interactions were found. The findings of this study suggest that regardless of environmental temperature soccer players cover the greatest total distance and LSA distance in the first half and especially in the first 15 minutes of the match. The environmental temperature had no effect on HSA distance, while total distance and LSA distance decreased more throughout the match in warm than in cool conditions. In conclusion, it appears that in warm environments soccer players are able to maintain similar high-intensity match-play as in cool conditions, at the expense of LSA.